Smart Structures and Materials 2005: Smart Sensor Technology and Measurement Systems 2005
DOI: 10.1117/12.606850
|View full text |Cite
|
Sign up to set email alerts
|

Pavement deflection vehicle weighing method with embedded piezoelectric sensor

Abstract: In weigh-in-motion (WIM) system, the gross weight or the axle weight of the passing vehicle can be measured dynamically by the sensors installed in or on the pavement. One of the WIM sensors is piezoelectric sensor. Although piezoelectric sensor has limited measurement accuracy, it is widely deployed for its low cost and easy installation. To use the piezoelectric sensor, several factors have to be considered for the WIM site itself to ensure the vehicle passing over the sensor with a relative stable state. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…AC-13 mixture mixes are shown in Table 1: The burial depth of the axle load sensor in asphalt concrete is a key factor affecting the monitoring accuracy. Studies have shown that axle load sensors embedded in the surface layer of the pavement have the best monitoring effect [34,35], but burial in the surface layer of the pavement with a serious disease is not conducive to the long-term service of the sensors [50][51][52][53]. Therefore, in this paper, the sensor base is embedded at the bottom of the rutting slab, and the top of the sensor is 2 cm from the surface layer of asphalt concrete after burial.…”
Section: Embedment and Dynamic Weighing In Asphalt Concrete Slabmentioning
confidence: 99%
“…AC-13 mixture mixes are shown in Table 1: The burial depth of the axle load sensor in asphalt concrete is a key factor affecting the monitoring accuracy. Studies have shown that axle load sensors embedded in the surface layer of the pavement have the best monitoring effect [34,35], but burial in the surface layer of the pavement with a serious disease is not conducive to the long-term service of the sensors [50][51][52][53]. Therefore, in this paper, the sensor base is embedded at the bottom of the rutting slab, and the top of the sensor is 2 cm from the surface layer of asphalt concrete after burial.…”
Section: Embedment and Dynamic Weighing In Asphalt Concrete Slabmentioning
confidence: 99%
“…On the basis of laboratory strain monitoring effectiveness of the sensor in asphalt concrete, the self-developed sensor was applied in practical pavement construction, aiming to verify its engineering performance [32,33]. The engineering field application of the self-developed sensor is shown in Figure 9.…”
Section: Application Of Self-developed Sensor In Practical Pavement I...mentioning
confidence: 99%